2004
DOI: 10.1016/j.ydbio.2004.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Axial patterning of C. elegans male sensilla identities by selector genes

Abstract: The fan and rays of the C. elegans male tail constitute a compound sensory organ essential for mating. Within this organ, the individual sensilla, known as rays, have unique identities. We show that ray identities are patterned by a selector gene mechanism in a manner similar to other serially homologous axial structures. One selector gene that promotes the identities of a subset of the rays is the Hox gene egl-5. Within EGL-5-expressing rays, further patterning is provided by a Pax-6 homolog and a signal of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
65
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 52 publications
4
65
0
Order By: Relevance
“…The concept can be applied to the level of individual cell types as well (for example, ref. 41). From this point of view, the cell-typespecific transcription factors cog-1, lin-11, and egl-38 can be thought of as selector genes for subsets of vulval cell types.…”
Section: Resultsmentioning
confidence: 99%
“…The concept can be applied to the level of individual cell types as well (for example, ref. 41). From this point of view, the cell-typespecific transcription factors cog-1, lin-11, and egl-38 can be thought of as selector genes for subsets of vulval cell types.…”
Section: Resultsmentioning
confidence: 99%
“…As described above, the orientation of ray openings alternate along the A-P axis, and ray pairs have a characteristic shape (Sulston and Horvitz, 1977;Sulston et al, 1980). Furthermore, A-and B-type neuron populations can be divided into subtypes based on neurotransmitter fate, and these fates are not exclusively paired with a given ray morphology (Sulston and Horvitz, 1977;Lints et al, 2004). These various features could confer functional specialization among different ray pairs.…”
Section: Introductionmentioning
confidence: 98%
“…In addition to dopamine and serotonin, C. elegans contains a complex profile of FMRFamide-like (FaRP) neuropeptide in RnB neurons (4). We found that the specification of FaRP neuronal fate is also affected in sor-3 and sop-2 mutants.…”
Section: Resultsmentioning
confidence: 85%
“…Each finger-like sensory ray consists of the dendritic endings of two distinct neurons, an A-type neuron (RnA) and a B-type neuron (RnB), wrapped in the process of a glial-like structural cell (Rnst) (where n stands for rays [1][2][3][4][5][6][7][8][9]. A subset of A-type neurons, R5A, R7A, and R9A, express the neurotransmitter dopamine, whereas a subset of B-type neurons, R1B, R3B, and R9B, express serotonin.…”
mentioning
confidence: 99%
See 1 more Smart Citation